Guanine Nucleotide Exchange Factor Independence of the G-protein eEF1A through Novel Mutant Forms and Biochemical Properties - Ozturk, Sedide B. (American Society for Biochemistry and Molecular Biology, 2008)
Most G-proteins require a guanine nucleotide exchange factor (GEF) to regulate a variety of critical cellular processes. Interestingly, a small number of G-proteins switch between the active and inactive forms without a GEF. Translation elongation factor 1A (eEF1A) normally requires the GEF eEF1Bα to accelerate nucleotide dissociation. However, several mutant forms of eEF1A are functional independent of this essential regulator in vivo. GEF-independent eEF1A mutations localize close to the G-protein motifs that are crucial for nucleotide binding. Kinetic analysis demonstrated that reduced GDP affinity correlates with wild type growth and high translation activities of GEF-independent mutants. Furthermore, the mutant forms show an 11–22-fold increase in rates of GDP dissociation from eEF1A compared with the wild type protein. All mutant forms have dramatically enhanced stability at elevated temperatures. This, coupled with data demonstrating that eEF1A is also more stable in the presence of nucleotides, suggests that both the GEF and nucleotide have stabilizing effects on eEF1A. The biochemical properties of these eEF1A mutants provide insight into the mechanism behind GEF-independent G-protein function.